Environmental Education Practices in Indonesia: A Review - Prayogo, Wisnu; Ratnaningsih, Wahyu; Suhardono, Sapta; Suryawan, I Wayan Koko (Journal of Sustainable Infrastructure, 2024)
This thorough analysis explores the situation of environmental education in Indonesia, looking at its historical development, present frameworks, and notable efforts. Effective environmental education is essential given the great variety and various ecosystems of Indonesia. Indonesia, the fourth most populated nation in the world, has environmental problems because of heavy resource exploitation, industrialization, and fast urbanization. There is an urgent need for strong environmental education since society needs to be raised with the information and abilities to actively support sustainable activities. This article tracks the development of Indonesia's environmental education policies, looking at their historical foundations and how they were incorporated into the country's formal educational system, including curriculum designs and instructional strategies. In addition to traditional schooling, the analysis highlights the roles played in raising environmental awareness by NGOs, neighborhood-based projects, and government cooperation. The review attempts to determine areas for improvement and evaluate the efficacy of current procedures by evaluating different approaches. Formulating ideas to improve environmental literacy and foster a more environmentally conscious society in Indonesia requires an understanding of the country's current strengths and weaknesses. This review contributes significantly to the current discussion on environmental education by highlighting the critical role that it plays in promoting a sustainable future for everyone, not just in Indonesia but also on a larger global scale.